The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1128/jmbe.v17i1.1022
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Online Citizen-Science Projects to Provide Experiential Learning Opportunities for Nonmajor Science Students

Abstract: Citizen science is becoming even more accessible to the general public through technological advances in the development of mobile applications, facilitating information dissemination and data collection. With the advent of “big data,” many citizen-science projects designed to help researchers sift through piles of research data now exist entirely online, either in the form of playing a game or via other digital avenues. Recent trends in citizen science have also focused on “crowdsourcing” solutions from the g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 2 publications
(2 reference statements)
0
9
0
Order By: Relevance
“…The focus for most of the papers in the final pool was either the scientific results from data collected by students (e.g., Cosentino et al 2014 , Riley et al 2020 ) or encouragement for instructors who may want to add citizen science to their courses (e.g., Voss and Cooper 2010 , Oberhauser and LeBuhn 2012 , Surasinghe and Courter 2012 , Kridelbaugh 2016 , Hardy and Hardy 2018 ). Only a small subset of the 15 papers was focused, even partially, on the results of assessments of student outcomes from their participation in citizen science.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The focus for most of the papers in the final pool was either the scientific results from data collected by students (e.g., Cosentino et al 2014 , Riley et al 2020 ) or encouragement for instructors who may want to add citizen science to their courses (e.g., Voss and Cooper 2010 , Oberhauser and LeBuhn 2012 , Surasinghe and Courter 2012 , Kridelbaugh 2016 , Hardy and Hardy 2018 ). Only a small subset of the 15 papers was focused, even partially, on the results of assessments of student outcomes from their participation in citizen science.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The educational outcomes of citizen science have been aligned with experiential education [27,33,34] and free-choice learning [35,36]. Experiential learning theory has been conceptualized in a variety of ways and is deemed to be a prominent learning method in adulthood [37,38].…”
Section: Capturing the Educational Outcomes Of Citizen Sciencementioning
confidence: 99%
“…Amidst this opportunity to cultivate a public understanding of science and environmental issues, the popularity of citizen science has exploded due to its contributory value to the research of scientists [24]. As practitioners continue to validate the contributions of citizen science as a field in its own right, researchers have increasingly sought to substantiate the educational potential of these programs for volunteers, now present in formal education at all levels [25][26][27][28][29][30][31][32]. The aim of this paper is to show how a pollinator conservation citizen science program provided an educational and experiential opportunity for volunteers to engage with a conservation issue and, perhaps more importantly, put the volunteers themselves in a position to raise awareness of and influence behavioral changes regarding pollinator conservation in their social spheres.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, many projects are designed with low barriers to entry, such as minimal time commitments, simplified data collection protocols, and everyday equipment like cell phone apps for data gathering or analysis (e.g., Bonney et al 2009;Golumbic, Baram-Tsabari, and Koichu 2020) that may make them attractive for non-major coursework. Studies of higher education students using CS have reported knowledge gains (e.g., Rosenberger and Aukema 2016), motivational changes (e.g., Kridelbaugh 2016), and deeper identification with science and science careers (e.g., Colón 2016) across a wide range of biology topics. For instance, an international survey of higher education instructors who use CS in their classes described science literacytype benefits, including greater efficacy in scientific thinking and greater knowledge of the applicability of scientific practice (Vance-Chalcraft et al 'in press').…”
Section: Introductionmentioning
confidence: 99%